Association between smoking status, toxicity and survival in the checkpoint inhibitor immunotherapy - Rudzińska, Anna; Juchaniuk, Pola; Oberda, Jakub; Krukowska, Kamila; Krzyśkowska, Sylwia; Kuchta, Eliza; Rodzajewska, Anna; Janiszewska, Mariola; Szklener, Katarzyna; Machulska-Ciuraj, Katarzyna; Rychlik-Grabowska, Monika; Urniaż, Aleksandra; et al. (Frontiers in Oncology, 2024)
IntroductionImmune checkpoint inhibitors (ICIs) have revolutionized cancer therapy by enhancing T-cell-mediated immune responses against tumors. However, their use can lead to immune-related adverse events (irAEs), impacting patient outcomes.MethodsThis single-center, observational study investigates the relationship between immune-related adverse events (irAEs) and survival outcomes in 151 patients treated with ICIs, with or without chemotherapy, at the Department of Clinical Oncology and Chemotherapy in the Independent Public Hospital No. 4 in Lublin. Statistical analyses were performed using the log-rank test, and multivariable Cox proportional hazard model (p < 0.05).ResultsIrAEs were observed in 38% of patients, with the most common being thyroid dysfunction (11.9%) and dermal toxicity (6.6%). Individual toxicity groups presented similar median values of “pack-years”, suggesting that smoking did not have a direct impact on the degree of toxicity. No relationship between the number of “pack-years” and the time of occurrence of toxicity symptoms and the number of toxicity sites was found. Smoking status did not have a moderating effect on the toxicity parameter in survival analysis (OS) and progression free survival analysis (PFS). Pack-years of smoking significantly impacted both OS (HR = 1.01, p = 0.014) and PFS (HR = 1.01, p = 0.011).DisscusionThe results suggested that smoking, measured in pack-years, had no appreciable effect on the amount of toxicity experienced by patients and no correlation between smoking status, irAEs and efficiency of the treatment was found. Despite results not reaching statistical significance, other potential mechanisms by which smoking may influence cancer treatment cannot be ruled out.